Multi-omics analysis of the tumor microenvironment after metastasis: advancing toward personalized immunotherapy and molecular targeted strategies - Gao, Qing; Wu, Huqiang; Duan, Li; Lv, Guanhua; Quan, Dongmei (Frontiers in Immunology, 2025)
The metastatic tumor microenvironment (TME) is a highly dynamic and heterogeneous ecosystem that plays a critical role in promoting cancer cell colonization, immune escape, and resistance to therapy. Recent advances in multi-omics technologies—including genomics, transcriptomics, epigenomics, proteomics, and metabolomics—have enabled a systems-level understanding of the molecular reprogramming that occurs in the TME following metastasis. In this review, we systematically summarize emerging findings from recent multi-omics studies that dissect cellular composition, signaling pathways, immune landscape, and metabolic rewiring within the metastatic TME. We highlight key molecular signatures and intercellular interactions that drive metastatic progression and therapy resistance. Furthermore, we discuss how integrative multi-omics data are being leveraged to identify actionable targets and to design novel immunotherapeutic and molecular precision strategies tailored to the metastatic niche. These insights provide a scientific rationale for the development of TME-targeted approaches in the treatment of advanced-stage cancers.